THERAPEUTIC APPROACH OF A CASE OF RHEUMATOID ARTHRITIS COMPLICATED WITH RENAL AMYLOIDOSIS IN A YOUNG WOMAN - Alexandra Burlui; Anca Cardoneanu; Luana Macovei; Claudia Banu; Elena Rezus (Romanian Journal of Rheumatology, 2017)
Systemic AA amyloidosis is an uncommon complication of rheumatoid arthritis (RA), especially in poorly controlled RA. Renal involvement caused by deposits of amyloid fibrils derived from acute-phase proteins is represented by nephrotic-range proteinuria ultimately leading to renal failure. We report the case of 27-year-old woman diagnosed with RA, with a history of musculoskeletal involvement since the age of 16, manifested by arthritis involving the wrists, knees and ankles; accompanied by severe and persistent inflammatory syndrome. She presented with an active form of RA complicated with secondary amyloidosis manifested by nephrotic-range proteinuria at the time of admission. Renal biopsy confirmed the presence of amyloid deposits. Anti-TNFα therapy with Certolizumab pegol proved effective in reducing proteinuria and inflammatory biomarker levels in our patient. The efficacy of anti TNF-α therapy in RA complicated with renal amyloidosis is demonstrated by recent scientific data.